Genetic diversity in modern T. Aman Rice varieties of Bangladesh (Oryza sativa L.) - Biswash, M.R.; Sharmin, M.; Rahman, N.M.F.; Farhat, T.; Siddique, M.A. (Penerbit Universiti Kebangsaan Malaysia, 2016)
A field experiment was conducted from June to December, 2013 to study the genetic diversity of 15 modern T. Aman rice varieties of Bangladesh (Oryza sativa L.) with a view to assess the superior genotype in future hybridization program for developing new rice varieties that is suitable for the target environment. Analysis of variance for each trait showed significant differences among the varieties. High heritability associated with high genetic advance in percent of mean was observed for plant height and thousand seed weight which indicated that selection for these characters would be effective. Hence, thrust has to be given for these characters in future breeding program to improve the yield trait in rice. Multivariate analysis based on 10 agronomic characters indicated that the 15 varieties were grouped into four distant clusters. The inter cluster distance was maximum between cluster II and cluster IV. The highest intra-cluster distance was found in cluster IV. Based on positive value of vector 1 and vector 2, plant height and 1000-seed weight had maximum contribution towards genetic divergence. From the results, it can be concluded that the varieties BRRI dhan40, BRRI dhan44, BRRI dhan46, BRRI dhan49 and BINA dhan7 may be selected for future hybridization program.